The effects of exit from work on health across different socioeconomic groups: A systematic literature review - Schaap, R.; de Wind, A.; Coenen, Pieter; Proper, K.; Boot, C. (Pergamon Press, 2018)
© 2017 Elsevier Ltd Exit from work leads to different effects on health, partially depending on the socioeconomic status (SES) of people in the work exit. Several studies on the effects of exit from work on health across socioeconomic groups have been performed, but results are conflicting. The aim of this review is to systematically review the available evidence regarding the effects of exit from work on health in high and low socioeconomic groups. A systematic literature search was conducted using Pubmed, Embase, Web of Science, CINAHL and PsycINFO. Search terms related to exit from work, health, SES and design (prospective or retrospective). Articles were included if they focused on: exit from work (early/statutory retirement, unemployment or disability pension); health (general, physical or mental health and/or health behaviour); SES (educational, occupational and/or income level); and inclusion of stratified or interaction analyses to determine differences across socioeconomic groups. This search strategy resulted in 22 studies. For general, physical or mental health and health behaviour, 13 studies found more positive effects of exit from work on health among employees with a higher SES compared to employees with a lower SES. These effects were mainly found after early/statutory retirement. In conclusion, the effects of exit from work, or more specific the effects of early/statutory retirement on health are different across socioeconomic groups. However, the findings of this review should be interpreted with caution as the studies used heterogeneous health outcomes and on each health outcome a limited number of studies was included. Yet, the positive effects of exit from work on health are mainly present in higher socioeconomic groups. Therefore, public health policies should focus on improving health of employees with a lower SES, in particular after exit from work to decrease health inequalities.